2020
DOI: 10.1371/journal.pone.0232915
|View full text |Cite
|
Sign up to set email alerts
|

Promoter choice: Who should drive the CAR in T cells?

Abstract: Chimeric antigen receptor (CAR) T cell therapy is an effective treatment for B cell malignancies, with emerging potential for the treatment of other hematologic cancers and solid tumors. The strength of the promoter within the CAR cassette will alter CAR-polypeptide levels on the cell surface of the T cell-impacting on the kinetics of activation, survival and memory cell formation in T cells. In addition to the CAR, promoters can be used to drive other genes of interest to enhance CAR T cell function. Expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…One recent study compared the lentiviral titer, transduction efficiency, marker and CAR expression levels, cytokine production (IL-2 and IFN-γ), and killing ability of four promoters, including EF-1 (EF-1A in our study), CMV, hPGK, and RPBSA. 14 EF-1 exhibited the best transduction efficiency, killing ability, and cytokine production. Consistent with our observations, these authors observed a reduction in CAR expression driven by the hPGK and RPBSA promoters, which retained acceptable killing ability but reduced cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recent study compared the lentiviral titer, transduction efficiency, marker and CAR expression levels, cytokine production (IL-2 and IFN-γ), and killing ability of four promoters, including EF-1 (EF-1A in our study), CMV, hPGK, and RPBSA. 14 EF-1 exhibited the best transduction efficiency, killing ability, and cytokine production. Consistent with our observations, these authors observed a reduction in CAR expression driven by the hPGK and RPBSA promoters, which retained acceptable killing ability but reduced cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study considered promoter choice when a long and complicated mRNA was used in gene therapy. 14 Four promoters, EF1A, CMV, hPGK, and RPBSA, were used to compare the packaging and transduction efficiencies, marker and CAR expression, cytokine production levels, and lytic abilities, and EF1A was best of these four promoters. However, MND (myeloproliferative sarcoma virus MPSV enhancer, negative control region NCR deletion, d1587rev primer binding site replacement) had good transcriptional ability in cancer cells in a 1997 study.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the MSCV outperformed both EF1α and PGK in terms of expression levels and CAR expression stability [ 35 ]; however, the promotor efficacy may be influenced by the scFv sequence itself [ 36 ] (see section Single-chain fragment variant (scFv) ). Given these and other studies [ 37 ] that report different optimal promoters, it is important to determine the optimal promoter for a given construct (that may also contain additional elements that influence expression levels, such as reporters) and viral vector. The latter is important, since the choice of a promoter also influences the virus titer.…”
Section: Car Structure Designmentioning
confidence: 99%
“…Recent reports suggest that CD95:CD95L signalling may play a role in the limited long-term persistence of CAR T cells in treating solid tumours [ 49 , 50 ]. Blockade of the signalling pathway has been shown to both increase CAR T cell persistence and number without adverse effects [ 49 , 50 , 51 , 52 , 53 ]. Inhibiting the CD95:CD95L pathway enhanced the CAR T cell therapy in vitro and in vivo.…”
Section: The Role Of Mitochondria In Cell Deathmentioning
confidence: 99%
“…The expression of genes involved in a particular metabolic pathway can be modulated using constitutive or inducible systems. The constitutive expression can be achieved using dual-promoter systems [ 132 ], bidirectional promoters [ 133 ], 2A self-cleaving peptides [ 52 ] or adding internal ribosome entry site (IRES) sequences [ 134 ]. For controlled expression over gene-of-interest (GOI), tetracycline (Tet)-On/Off system [ 135 ] or endogenous inducible promoters (e.g., IL-2 minimal promoter) [ 136 ] can be employed.…”
Section: Strategies To Improve Car T Cell Therapy By Metabolic Repmentioning
confidence: 99%